Development and validation of a reverse phase-high performance liquid chromatography method for estimation of Thiamine diphosphate in whole blood and dried blood spot - Ysphaneendra Mallimoggala, Monalisa Biswas, Nihaal Maripini, Varashree Bolar Suryakanth, Revathi P. Shenoy, Leslie Edward S. Lewis (Journal of Applied Pharmaceutical Science, 2025)
Thiamine deficiency is a long-standing yet unresolved problem, especially in South Asian countries, which can manifest as acute life-threatening sequalae. However, there is a paucity of feasible and cost-effective analytical methods to assess circulating thiamine diphosphate (TDP) in clinical settings. The study aimed to develop a validated, cost effective, reliable, and reproducible high performance liquid chromatography (HPLC) method for the estimation of TDP in whole blood and dried blood spot (DBS) matrix. The study aimed to arrive at a method with minimum sample extraction steps employing simple solvents, short pre-processing and analysis time, extended column life [Luna® C18(2), 5 μm, 50 × 3.0 mm HPLC column], and a sustainable green chemistry approach. The reverse phase-HPLC-fluorescence method developed to detect the thiochrome derivative of TDP showed excellent specificity, good linearity (10–250 ng/ml), and accuracy, precision, and recovery (87.8%–101.18% for whole blood and 95.2%–123% for DBS), well within acceptable limits. The developed method showed good agreeability between whole blood and DBS matrix, the method was further validated by the assessment of third-party matrix-matched quality control material. This method could be implemented in clinical diagnostics for screening, and diagnosis of thiamine deficiency using both whole blood and DBS matrix, aiding in early therapeutic supplementation of thiamine, which can prevent fatal adversities due to acute thiamine deficiency.
Keywords: Thiamine, thiamine diphosphate, dried blood spot, whole blood, HPLC, screening